PENGARUH PERKEMBANGAN KARIER TERHADAP PRESTASI KERJA PEGAWAI PADA KANTOR DESA KARANG BINANGUN BELITANG MADANG RAYA OGAN KOMERING ULU TIMUR - Dwi Ashraf, Muhammad (Jurnal Trisna Riset, 2025)
The availability of quality human resources who have a high work ethic is the main capital for an organization to be able to compete with other organizations. Without the initiative of each individual to try to move forward without having to be pushed, the organization will not have any meaning. At the Karang Binangun Belitang Madang Raya Ogan Komering Ulu Timur Village Office, it turns out that employee career development has not been implemented well so that employee work performance is not optimal. The problem faced in this research is how career development influences employee work performance at the Karang Binangun Belitang Madang Raya Ogan Komering Ulu Timur Village Office. The aim of this research is to identify the influence of career development on employee work performance in the office, as well as as a reference for further research regarding career development and employee work performance. The hypothesis proposed is that career development has a positive influence on employee work performance at the Karang Binangun Belitang Madang Raya Ogan Komering Ulu Timur Village Office. Methods for collecting and processing data using library studies and field studies using observation, questionnaires, interviews and documentation. From the results of the discussion, it was found that the correlation between Career Development in an effort to improve employee work performance at the Karang Binangun Belitang Madang Raya Ogan Komering Ulu Timur Village Office obtained an r figure of 0.6. After consulting with conservative standards, it is between 0.600 - 0.799 which is considered a strong correlation. So it can be said that there is a strong influence between career development on employee work performance at the Karang Binangun Belitang Madang Raya Ogan Komering Ulu Timur Village Office